Identification of the Host Substratome of Leishmania-Secreted Casein Kinase 1 Using a SILAC-Based Quantitative Mass Spectrometry Assay - Smirlis, Despina; Dingli, Florent; Sabatet, Valentin; Roth, Aileen; Knippschild, Uwe; Loew, Damarys; Späth, Gerald F.; Rachidi, Najma (Frontiers in Cell and Developmental Biology, 2022)
Leishmaniasis is a severe public health problem, caused by the protozoan Leishmania. This parasite has two developmental forms, extracellular promastigote in the insect vector and intracellular amastigote in the mammalian host where it resides inside the phagolysosome of macrophages. Little is known about the virulence factors that regulate host-pathogen interactions and particularly host signalling subversion. All the proteomes of Leishmania extracellular vesicles identified the presence of Leishmania casein kinase 1 (L-CK1.2), a signalling kinase. L-CK1.2 is essential for parasite survival and thus might be essential for host subversion. To get insights into the functions of L-CK1.2 in the macrophage, the systematic identification of its host substrates is crucial, we thus developed an easy method to identify substrates, combining phosphatase treatment, in vitro kinase assay and Stable Isotope Labelling with Amino acids in Cell (SILAC) culture-based mass spectrometry. Implementing this approach, we identified 225 host substrates as well as a potential novel phosphorylation motif for CK1. We confirmed experimentally the enrichment of our substratome in bona fide L-CK1.2 substrates and showed they were also phosphorylated by human CK1δ. L-CK1.2 substratome is enriched in biological processes such as “viral and symbiotic interaction,” “actin cytoskeleton organisation” and “apoptosis,” which are consistent with the host pathways modified by Leishmania upon infection, suggesting that L-CK1.2 might be the missing link. Overall, our results generate important mechanistic insights into the signalling of host subversion by these parasites and other microbial pathogens adapted for intracellular survival.